2017
DOI: 10.15296/ijwhr.2017.34
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Matricaria chamomilla Extract on Histological Damage and Oxidative Stress Induced by Torsion/Detorsion in Adult Rat Ovary

Abstract: Introduction Ovarian torsion is one of the prevalent gynecologic emergencies, in which the adnexal components swing around their axis that leads to obstruction of arterial, venous, and/or lymphatic vessels (1). In this situation, gangrene and necrosis with the expansion of arterial insufficiency is followed by primary congestion and hemorrhagic infarction owing to venous and lymphatic obstruction. However, there is no data about the least number of turns to form the torsion and also there is no data for the du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 15 publications
(24 reference statements)
6
64
1
Order By: Relevance
“…These changes of MDA, GPX and SOD levels in T/D group were also observed in similar studies that treatment with some antioxidant substances like verapamil, onion juice, Matricaria chamomilla, thymoquinone and quercetin could improve this biochemical condition to approximately healthy condition (Aktoz, Kanter, & Aktas, 2010;Ameli et al, 2018;Ayan et al, 2016;Shokoohi, Madarek, et al, 2018;Soltani et al, 2018). There are two major limitations in this study.…”
Section: Stevia Rebaudiana Is a Shrub With Numerous Medical Featuressupporting
confidence: 76%
See 1 more Smart Citation
“…These changes of MDA, GPX and SOD levels in T/D group were also observed in similar studies that treatment with some antioxidant substances like verapamil, onion juice, Matricaria chamomilla, thymoquinone and quercetin could improve this biochemical condition to approximately healthy condition (Aktoz, Kanter, & Aktas, 2010;Ameli et al, 2018;Ayan et al, 2016;Shokoohi, Madarek, et al, 2018;Soltani et al, 2018). There are two major limitations in this study.…”
Section: Stevia Rebaudiana Is a Shrub With Numerous Medical Featuressupporting
confidence: 76%
“…(Chatsudthipong & Muanprasat, 2009;Jayaraman et al, 2008;Shivanna et al, 2013;Shukla et al, 2013Shukla et al, , 2009Tadhani et al, 2007;Tadhani & Subhash, 2006;Takahashi et al, 2001). (2018), Shokoohi, Madarek, et al (2018) and Soltani et al (2018) in separated studies indicated that I/R injury is accompanied by destruction in tissue morphology and reduction of MTBS, and this situation can be reversed by use of a material with antioxidant features (Ameli et al, 2018;Shokoohi, Madarek, et al, 2018;Soltani et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous studies (Moghimian, Soltani, Abtahi, & Shokoohi, ; Soltani, Moghimian, Abtahi, & Shokoohi, ), the serum level of malondialdehyde (MDA) was measured by placing 0.20 cm³ of serum into a microtube containing 3.0 cm³ of glacial acetic acid, to which 3.0 cm³ of 1% TBA in 2% NaOH was added. The microtube containing the mixture was placed in boiling water for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Such sensitivity influences the process of spermatogenesis, leading to the impairment in fertility. The evaluation of the properties of seminiferous tubules, that is, morphological and morphometric parameters is a simple method for the assessment of the changes in the spermatogenesis process (Altoé et al, ; Soltani et al, ). The spermatogenic process could be decreased by detrimental alterations in the function of stem cells, resulting in degeneration of spermatogonial cells and phagocytosis by Sertoli cells.…”
Section: Discussionmentioning
confidence: 99%